Relación de altura total y comercial con el diámetro de los árboles en un bosque de terraza baja de la comunidad nativa Nuevo Libertad, distrito del Napo, Loreto, 2022 - Vacalla Ochoa, Jesus (2023)
The relationship between the total height and the commercial height and the diameter of the trees in a low terrace forest, district of Napo, Loreto, Peru, was determined. Data from the forestry census of the commercial species of the operational plan (PO) 1 of the cutting plot (PC) 1 of the PC1 for forest use permits in native communities and peasant communities were evaluated. The results show that the quadratic distribution model corresponds to the average total diameter-height relationship (Y=24.624 (-0.024 x DAP)+(0.000 x DAP2)) (r=0.868, R2=0.754), average commercial diameter-height (Y= 18.619 (-0.021 x DAP)+(0.000 x DAP2)) (r=0.859, R2=0.738), average total diameter-height of the species Maquira coriaceae “capinuri” (Y=22.368 (0.108 x DAP)+ (-0.001 x DBH2)) (r=0.729, R2=0.532) and average commercial diameter-height of the species Maquira coriaceae “capinuri” (0.072 x DBH)+(-0.001 x DBH2)) (r=0.695, R2= 0.484). Statistically, there is a regular negative correlation between the total height (r=-0.050) and commercial height (r=-0.082) with the diameter of the trees.